Defect Reduction Analysis to Improve Glass Bottle Packaging Products Quality Using Statistical Process Control (SPC) at PT. Muliaglass Container (MGC) - Tukhas Shilul Imaroh; Ali Mustofa (Journal of Social Science, 2022)
Quality plays an important role, problems in the number of defects in production cause a decrease in quality. To prevent this increase in defective products, it is necessary to evaluate the most types of defects to determine the causes of defects so that corrective actions are obtained using statistical process control (SPC) methods and with 3 Pareto diagram controllers, control charts and fishbones. This research is intended to explore facts about Defect Reduction Through Statistical Process Control (SPC) for Product Quality Improvement and Supervision and to help determine the views on reducing the number of defects in products so as to increase the target of good product quality. The implementation of the results of this study shows a fairly good reduction in production defects based on the calculation results, namely before repairs from January to March 2021 total sales are 550,962 pc and after repairs in January to March 2022 a total of 496,260 pc so there is a decrease of 10% (54,702 pc). ) with a cost saving value of Rp. 59,318,001/mon.